(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
This article delves into the clinical anatomy of key neck organs, namely the submandibular salivary gland, larynx, and esophagus. Through a thorough literature analysis, this study aims to provide a comprehensive understanding of these structures, their functions, and their clinical significance. The methods section outlines the approach taken for data collection and analysis. Results present key findings, while the discussion interprets these results within the broader context of clinical practice. Conclusions are drawn based on the study’s outcomes, accompanied by suggestions for future research in this field.